INTRACELLULAR STARCH FORMATION IN CORYNEBACTERIA - Carrier, E. Bernard (1962)
Carrier, E. Bernard (Louisiana State University, Baton Rouge, La.) and C. S. McCleskey. Intracellular starch formation in cor-yne bacteria. J. Bacteriol. 83:1029–1036. 1962.—Cor-ynebacterium tritici, C. striatum, C. renale, and C. pseudodiphtheriticum produce an intracellular starch-like material when grown on native starches; glucose-1-phosphate, mono-, di-, and trisaccharides do not serve as substrates for intracellular starch formation. C. pseudotuberculosis and C. kutscheri produce intracellular starch from starch substrates and glucose-1-phosphate. C. diphtheriae produces starch from glucose-1-phosphate only.